The Clinicopathologic Features and Treatment of 607 Hindgut Neuroendocrine Tumor (NET) Patients at a Single Institution. Issue 19 (May 2016) - Kim, Seung Tae; Ha, Sang Yun; Lee, Jeeyun; Hong, Sung No; Chang, Dong Kyung; Kim, Young Ho; Park, Yoon Ah; Huh, Jung Wook; Cho, Yong Beom; Yun, Seong Hyeon; Lee, Woo Yong; Kim, Hee Cheol; et al.
Abstract : Abstract: The clinicopathologic features of hindgut neuroendocrine tumor (NET) as well as the treatment outcomes are not well known. There are currently no published data on treatment outcomes for patients with metastatic hindgut NET. The aim of this study was to conduct a comprehensive analysis of clinicopathologic features, treatments and survival in hindgut NET patients. Among patients who were pathologically diagnosed with hindgut NET at Samsung Medical Center between March 2001 and February 2015, 607 were analyzed in this study. Hindgut NETs were defined as NETs that originated from the transverse and distal colon, rectum, and anus. Primary sites included 81 colon (13.3%) and 526 rectum (86.7%). According to the WHO classification, 578 patients (95.2%) had grade 1 NETs, 17 (2.8%) grade 2 NETs, and 12 (2.0%) had neuroendocrine carcinoma (NEC). Forty-two patients (6.9%) had extensive disease, while the majority (93.1%, 565 patients) only exhibited localized disease. The 5- and 10-year survival rates of 565 localized NET patients were 98.1% and 95.3%, respectively. The median OS in 42 patients with extensive disease was 24.8 months (95% CI, 10.7–38.8). Among 565 patients with localized disease, the majority (484 patients, 85.7%) were treated with endoscopic procedure by gastroenterologists. For 42 patients with extensive disease, 17 patients were managed by supportive care, 3 by concurrent chemoradiotherapy (CCRT), and 22 by systemic therapy. Among these 22 patients, 12 patients received only first-line therapy, 8 had second-line, and only 2 patients had third-line therapy. As first-line chemotherapy, the most commonly used regimens were etoposide plus cisplatin (N = 7) and long acting octreotide (N = 7). During treatment courses, the most commonly used regimen was long-acting octreotide. The median OS in 22 metastatic NET patients receiving systemic therapy was 19.3 months (95% CI, 3.2–35.3). Multivariate analysis in all 607 hindgut NETs patients suggested that the extent and the primary site of disease were significant independent prognostic factors for long term survival. This analysis provides useful information about the clinicopathologic features, treatments and survival outcomes for hindgut NET patients.